2022
DOI: 10.3390/atmos13060898
|View full text |Cite
|
Sign up to set email alerts
|

Future Climate Projections Using SDSM and LARS-WG Downscaling Methods for CMIP5 GCMs over the Transboundary Jhelum River Basin of the Himalayas Region

Abstract: Climate change is one of the leading issues affecting river basins due to its direct impacts on the cryosphere and hydrosphere. General circulation models (GCMs) are widely applied tools to assess climate change but the coarse spatial resolution of GCMs limit their direct application for local studies. This study selected five CMIP5 GCMs (CCSM4, HadCM3, GFDL-CM3, MRI-CGCM3 and CanESM2) for performance evaluation ranked by Nash–Sutcliffe coefficient (NSE) and Kling–Gupta Efficiency (KGE). CCSM4 and HadCM3 large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
(46 reference statements)
2
8
0
Order By: Relevance
“…(Shayanmehr et al, 2022). The graphic comparison of mean observed and simulate data was also done to see the ability of the model to downscale future Prec., Tmin and Tmax as indicated in figure 3 (Munawar et al, 2022;Zubaidi et al, 2019). The graphical representations demonstrated that LARS-WG effectively replicated the observed Prec., Tmin, and Tmax, indicating the model's capability to downscale climate variables in the study area.…”
Section: Evaluating the Simulation Performance Of Lars-wgmentioning
confidence: 53%
See 2 more Smart Citations
“…(Shayanmehr et al, 2022). The graphic comparison of mean observed and simulate data was also done to see the ability of the model to downscale future Prec., Tmin and Tmax as indicated in figure 3 (Munawar et al, 2022;Zubaidi et al, 2019). The graphical representations demonstrated that LARS-WG effectively replicated the observed Prec., Tmin, and Tmax, indicating the model's capability to downscale climate variables in the study area.…”
Section: Evaluating the Simulation Performance Of Lars-wgmentioning
confidence: 53%
“…(10) to (13). These metrics are employed to compare the simulated values of Prec., Tmin and Tmax with their corresponding observed values (Ahmadi et al, 2021;Baez-Villanueva et al, 2018;Munawar et al, 2022;Shayanmehr et al, 2022). Models that exhibit higher values of R 2 and Kling-Gupta efficiency (KGE) and lower values of RMSE and MAD demonstrate good performance in simulating future climate variables.…”
Section: Performance Evaluation Of Lars-wgmentioning
confidence: 81%
See 1 more Smart Citation
“…Initially, the daily rainfall data were computed and converted to monthly, seasonal and total annual. For future projections of precipitation for the 21st century, GCM CCSM4 (Community Climate System Model version 4) has been selected following the methodology as presented in the author's previous research (Munawar et al 2022a). The daily large-scale predictors of GCM CCSM4 for RCP4.5 and RCP8.5 and the daily predictors for NCEP (National Centers for Environmental Prediction) were downloaded from a website (http://climate-scenarios.canada.ca/).…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Despite improvements in the GCMs efficiency to represent climate processes in better ways these uncertainties cater to produce better climate projection but remain a subject of ample concern at the regional/local level (Hussain et al 2021). To cope with these uncertainties, downscaling techniques have been widely applied (Munawar et al 2022a). GCMs' coarse spatial resolution limits their use for sustainable environmental management (Araya-Osses et al 2020).…”
Section: Introductionmentioning
confidence: 99%